The PPARα Agonist Fenofibrate Prevents Formation of Protein Aggregates (Mallory-Denk bodies) in a Murine Model of Steatohepatitis-like Hepatotoxicity - Nikam, Aniket; Patankar, Jay; Somlapura, Meghana; Lahiri, Pooja; Sachdev, Vinay; Kratky, Dagmar; Denk, Helmut; Zatloukal, Kurt; Abuja, Peter M. (Scientific Reports, 2018)
Chronic intoxication of mice with the porphyrinogenic compound 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC) leads to morphological and metabolic changes closely resembling steatohepatitis, a severe form of metabolic liver disease in humans. Since human steatohepatitis (both the alcoholic and non-alcoholic type) is characterized by reduced expression of PPARα and disturbed lipid metabolism we investigated the role of this ligand-activated receptor in the development of DDC-induced liver injury. Acute DDC-intoxication was accompanied by early significant downregulation of Pparα mRNA expression along with PPARα-controlled stress-response and lipid metabolism genes that persisted in the chronic stage. Administration of the specific PPARα agonist fenofibrate together with DDC prevented the downregulation of PPARα-associated genes and also improved the stress response of Nrf2-dependent redox-regulating genes. Moreover, oxidative stress and inflammation were strongly reduced by DDC/fenofibrate co-treatment. In addition, fenofibrate prevented the disruption of hepatocyte intermediate filament cytoskeleton and the formation of Mallory-Denk bodies at late stages of DDC intoxication. Our findings show that, like in human steatohepatitis, PPARα is downregulated in the DDC model of steatohepatitis-like hepatocellular damage. Its downregulation and the pathomorphologic features of steatohepatitis are prevented by co-administration of fenofibrate.
Created from Fastlane, Scopus look-up